2021
DOI: 10.1007/s11864-021-00870-z
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Microsatellite Instability: Evolving Strategies Integrating Immunotherapy for Microsatellite Stable Colorectal Cancer

Abstract: Opinion statementAdvanced colorectal cancer (CRC) is a heterogeneous disease, characterized by several subtypes with distinctive genetic and epigenetic patterns. During the last years, immune checkpoint inhibitors (ICIs) have revamped the standard of care of several tumors such as non-small cell lung cancer and melanoma, highlighting the role of immune cells in tumor microenvironment (TME) and their impact on cancer progression and treatment efficacy. An “immunoscore,” based on the percentage of two lymphocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 100 publications
0
12
0
Order By: Relevance
“…First, MSI status serves as a diagnostic tool to help identify colorectal cancers arising from a possible familial setting (e.g. Lynch syndrome) 2 . Second, in general, patients with stage II colorectal cancers seem to derive a survival benefit with MSI 3 .…”
Section: Introductionmentioning
confidence: 99%
“…First, MSI status serves as a diagnostic tool to help identify colorectal cancers arising from a possible familial setting (e.g. Lynch syndrome) 2 . Second, in general, patients with stage II colorectal cancers seem to derive a survival benefit with MSI 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, current studies aim to identify predictive markers to improve patient stratification and to establish combination strategies for improving efficacy, especially in patients with pMMR tumors. Several studies are testing combination strategies of checkpoint inhibitors with chemotherapy, radiation, anti-VEGF antibodies, anti-EGFR antibodies, inhibitors of mitogen-activated protein kinase (MAPK) signaling, or multi-tyrosine kinase inhibitors aiming to turn immunologically ‘cold’ tumors into ‘hot’ tumors and thereby making them susceptible to immunotherapies (reviewed in Pecci et al 91 and Hirano et al, 80 Figure 1 ).…”
Section: Msi and Checkpoint Inhibitorsmentioning
confidence: 99%
“…With respect to immunotherapy, the pathway has been implicated in tumor–immune interaction in multiple ways, including regulation of immunosuppression through cytokines and growth factors, regulation of human leukocyte antigen (HLA) expression and thereby immune cell evasion from the tumor microenvironment. 91 The combination of atezolizumab with MEK inhibition using cobimetinib, however, led to disappointing efficacy in the phase III IMblaze370 trial, analyzing 363 pretreated patients: the combination led to an OS of 8.9 months compared with 7.1 months for atezolizumab alone and 8.5 months with the control treatment regorafenib. 103 Clinical trials combining checkpoint inhibitors with EGFR antibodies cetuximab and panitumumab with and without chemotherapy are ongoing.…”
Section: Msi and Checkpoint Inhibitorsmentioning
confidence: 99%
“…MiR-148a-3p and miR-448 respectively down-regulate the expression of calnexin (CANX) and indoleamine 2,3-dioxygenase 1 (IDO1), which enhances CD8 + T cell-mediated immune response in CRC (67,68). Cetuximab can induce ADCC by binding to EGFR on cancer cells and CD16 receptor on natural killer (NK) cells and dendritic cells (DCs) (69)(70)(71). It stimulates the production of proinflammatory cytokines, such as IFN-g and TNF-a, and activates cytotoxic T cells in the TME, thereby exerting tumor immunosuppressive effects (69)(70)(71).…”
Section: Impact Of Mirnas On Tumor Immune Microenvironmentmentioning
confidence: 99%
“…Cetuximab can induce ADCC by binding to EGFR on cancer cells and CD16 receptor on natural killer (NK) cells and dendritic cells (DCs) (69)(70)(71). It stimulates the production of proinflammatory cytokines, such as IFN-g and TNF-a, and activates cytotoxic T cells in the TME, thereby exerting tumor immunosuppressive effects (69)(70)(71). It has been suggested that anti-EGFR therapy and immunotherapy have synergetic and complementary mechanisms.…”
Section: Impact Of Mirnas On Tumor Immune Microenvironmentmentioning
confidence: 99%